Uma docência pela garimpagem: encontros com signos - Neuscharank, Angelica (2015)
This is a master s thesis written under the view of teaching anxieties and experimentations in relation to some spaces and meetings with signs produced by people, readings, conversations, life situations and fragments of the places where I have made myself as a teacher, student and reader. With the intention to capture the heterogeneous which were present in the meetings with the three schools, master s lectures, the meetings with the Group of Studies and Research in Art, Education and Culture and Proust readings. Such movements were weaved in order to think a mining teaching and a learning by the meeting with the signs (DELEUZE, 2010), which are concepts I problematize along this writing. Also, the tensioning with other concepts such as: heterogeneous, happening, cartographic attention and involuntary memory have been necessary. These concepts compose, along with the cartographic method, a possibility for what I designate as a mining of signs. Therefore, I have not concentrated on the exercise of the recent memory as a rescue, but as an involuntary memory, which allowed to overfly certain happenings and, thus, potentiate something that was already naturalized.